THE EFFECT OF PERSON-ORGANIZATION FIT, JOB SATISFACTION, AND TRUST TOWARD HIGH SCHOOLS’ TEACHERS AFFECTIVE COMMITMENT - Hamidah Hamidah; Mukhnery Mukhtar; Neti Karniati (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2017)
This study aims to determine the effect of a positive direct independent variables such as: person-organization fit, job satisfaction and trust in the dependent variable is the affective commitment high schoolsâ€™ teachers in Depok. Studies have been conducted on senior high school teachers in Depok. The method used was a survey with data analysis techniques using path analysis. Respondents are 194 of the total 376 senior high schoolsâ€™ teachers in Depok. They were selected by random sampling. The results of the study are as follows: (1) there was a direct effect of person-organization fit toward affective commitment, (2) there was a direct effect of  job satisfaction toward affective commitment, (3) there was a direct effect of  trust toward affective commitment, (4) there was a direct effect of  person-organization fit toward job satisfaction, (5) there was a direct effect of  person-organization fit toward trust. the conclusion is that the affective commitment is influenced by the person-organization fit, job satisfaction and trust.Keywords: Affective commitment , person-organization fit, job satisfaction and trust